The Effect of Kembang Leson Essential Oil on Locomotor Activity of Mice (Mus Musculus L.) Balb-C - Suwartiningsih, Nurul; Idham, Raja Ahmad; Pratiwi, Ambar (Proceeding International Conference on Science and Engineering, 2021)
Abstract. Kembang leson essential oil is known to have a relaxing effect so that it can be used as aromatherapy to treat psychological problems. The research was carried out to determine the effect of kembang leson essential oil on locomotor activity of mice (Mus musculus L.) Balb-C. The essential oil was isolated with Stahl steam and tested on Balb-C mice with a volume of 0.1 mL, 0.2 mL and 0.5 mL. A paired sample T-test is done to test the average difference between pre-treatment and post-treatment data. ANOVA test is done to test the average difference in post-treatment locomotor activity in each volume. The results show that kembang leson essential oil can increase swimming endurance along with decreasing immobility time and decreasing cage rotation which statistically significant between pretreatment and post-treatment. The most optimum volume of essential oil influenced locomotor activity is 0.5 mL, with an increase in swimming endurance up to 74.40% and a decrease in the rotary cage up to 50%. Kembang leson essential oil can affect the locomotor activity of Balb-C mice so that it can be developed into pharmaceutical preparations for aromatherapy.